Sustainability of hydropower as source of renewable and clean energy - Luis J.; Sidek L.M.; Desa M.N.M.; Julien P.Y. (Institute of Physics Publishing, 2023)
Hydroelectric energy has been in recent times placed as an important future source of renewable and clean energy. The advantage of hydropower as a renewable energy is that it produces negligible amounts of greenhouse gases, it stores large amounts of electricity at low cost and it can be adjusted to meet consumer demand. This noble vision however is becoming more challenging due to rapid urbanization development and increasing human activities surrounding the catchment area. Numerous studies have shown that there are several contributing factors that lead towards the loss of live storage in reservoir, namely geology, ground slopes, climate, drainage density and human activities. Sediment deposition in the reservoir particularly for hydroelectric purposes has several major concerns due to the reduced water storage volume which includes increase in the risk of flooding downstream which directly effects the safety of human population and properties, contributes to economic losses not only in revenue for power generation but also large capital and maintenance cost for reservoir restorations works. In the event of functional loss of capabilities of a hydropower reservoir as a result of sedimentation or siltation could lead to both economical and environmental impact. The objective of this paper is aimed present the importance of hydropower as a source of renewable and clean energy in the national energy mix and the increasing challenges of sustainability. Published under licence by IOP Publishing Ltd.